1997
DOI: 10.1021/bi970543u
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Potential Zinc-Binding Residues in the Active Site of the Enterococcal d-Ala-d-Ala Dipeptidase VanX

Abstract: VanX, one of the five proteins required for the vancomycin-resistant phenotype in clinically pathogenic Enterococci, is a zinc-containing d-Ala-d-Ala dipeptidase. To identify potential zinc ligands and begin defining the active site residues, we have mutated the 2 cysteine, 5 histidine, and 4 of the 28 aspartate and glutamate residues in the 202 residue VanX protein. Of 10 mutations, 3 cause inactivation and greater than 90% loss of zinc in purified enzyme samples, implicating His116, Asp123, and His184 as zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 30 publications
7
99
0
Order By: Relevance
“…RpoS is required for the recovery of the D-Ala-D-Ala dipeptide because it controls the expression of both the peptidase and the transport system (39). Control over the expression of cell wall remodeling enzymes is critical for cell integrity (40)(41)(42). Finally, the increased synthesis of MS channels upon entry into stationary phase may represent a component of the coordinated modification of the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…RpoS is required for the recovery of the D-Ala-D-Ala dipeptide because it controls the expression of both the peptidase and the transport system (39). Control over the expression of cell wall remodeling enzymes is critical for cell integrity (40)(41)(42). Finally, the increased synthesis of MS channels upon entry into stationary phase may represent a component of the coordinated modification of the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Biotinylated Recombinant Proteins-AviTag, a specific peptide sequence that can be biotinylated with biotin ligase, was cloned into a pIAD16 vector (18) to generate a pIAD16Avi plasmid. APP fragments with FLAG tag were inserted into the pIAD16Avi vector.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of ShhN was determined 15 years ago (Hall et al 1995), and revealed an unanticipated homology with zinc hydrolases ( Fig. 2A,B; Dideberg et al 1982;McCafferty et al 1997;Bochtler et al 2004). In ShhN and related zinc hydrolases, a zinc ion is coordinated by two histidines and an aspartate at the base of a large cleft.…”
Section: Hh Structurementioning
confidence: 99%